Chemical composition, antioxidant and antisalmonella activity of Mangifera indica L. flower and seed kernel extracts (International Current Pharmaceutical Journal, 2016)
The extracts obtained from flower and seed parts of Mangifera indica L. were investigated for antioxidant and antisalmonella activities. Disc diffusion assay and broth macrodilution method were used to determine the antisalmonella activity. However, DPPH assay used to determine antioxidant activities of petroleum ether, chloroform, acetone and ethanol extracts of flower and seed kernel of Mangifera indica L. The mineral content of different parts of Mangifera indica L. was determined using ICP-OES method. Seed kernel and flower were found to be the rich source of Fe with the concentration of 660.50 and 221.75 µg per gram of dry weight. The antioxidant activity of the extracts was determined by DPPH free radical scavenging method. The petroleum ether extract of flower and ethanol extract of flower exhibited the most significant antisalmonella activity with the lowest MIC value of 8 mg/ml. The highest antioxidant activity was recorded in petroleum ether seed kernel and chloroform flower extract with the percentage inhibition of 86.64 ± 2.49 and 79.80 ± 1.28, respectively. Among all the tested combinations chloroform flower and ethanol seed kernel extracts showed greater synergistic effect along with tetracycline against Salmonella typhi isolates. Four different compounds with dual property of antioxidant and antisalmonella were isolated from the petroleum ether seed kernel and acetone flower extracts using thin layer chromatography. GC-MS analysis of acetonic flower extract showed the presence of 1, 2-Benzenedicarboxylic acid, isodecyl octyl ester (Synonym: Phthalic acid). Compounds Oleic acid and eicosyl ester were found in petroleum ether seed kernel extract. The present study revealed that identified compounds are responsible for exhibiting antioxidant and antisalmonella activities in flower and seed kernel. These findings may justify the conventional use of Mangifera indica L. in the treatment of typhoid fever.Kamble et al., International Current Pharmaceutical Journal, September 2016, 5(10): 82-93http://www.icpjonline.com/documents/Vol5Issue10/02.pdf